106k views
3 votes
What term can you add to


(5)/(6) x - 4
to make it equivalent to

(1)/(2) x - 4


User JohnKiller
by
6.1k points

1 Answer

3 votes

9514 1404 393

Answer:

-1/3x

Explanation:

We want to find the term 'a' such that ...

(5/6x -4) + a = (1/2x -4)

Add 4-1/2x to both sides.

(5/6 -1/2)x -4 +4 +a = 0

(5/6 -3/6)x + a = 0 . . . . . . express the fractions using a common denominator

1/3x + a = 0 . . . . . . . . . . simplify the difference

a = -1/3x . . . . . . . . . . .subtract 1/3x

The term you can add to make the desired equivalent is -1/3x.

User Mkiever
by
5.1k points